Thirsty mermaids - Leyh, Kat (Gallery 13, 2021)
"Fresh out of shipwreck wine, three tipsy mermaids decide to magically masquerade as humans and sneak onto land to indulge in much more drinking and a whole lot of fun in the heart of a local seaside tourist trap. But the good times abruptly end the next morning as, through the haze of killer hangovers, the trio realizes they never actually learned how to break the spell, and are now stuck on land for the foreseeable future. Which means everything from: enlisting the aid of their I-know-we-just-met-can-we-crash-with-you bartender friend, struggling to make sense of the world around them, and even trying to get a job with no skill set ... all while attempting to somehow return to the sea and making the most of their current situation with tenacity and camaraderie (especially if someone else is buying)."--Amazon.